Quantifying elephant mortality in a changing landscape: insights from Jharkhand, India - Pandey, Ramesh Kumar; Roy, Kalpana; G., Athira N.; Dutta, Ananya; Mittal, Dheeraj; Nigam, Parag; Nath, Anukul; Habib, Bilal (Frontiers in Ecology and Evolution, 2025)
Elephant mortality in Jharkhand has reached critical levels, primarily driven by anthropogenic pressures and habitat degradation, which has intensified their movement into human-dominated landscapes. We conducted a comprehensive analysis of elephant mortality trends in Jharkhand, India, spanning from 2000 to 2023. This study investigates the influence of habitat alterations, anthropogenic activities, and other ecogeographical factors on the escalating elephant mortality in the region. In the last 23 years, forest cover has changed up to 6% and subsequently, built-up areas have risen by 39.34%, further encroaching on elephant habitats and corridors. During the period a total of 225 elephant deaths were reported, with 152 of these caused by various anthropogenic activities and highest death was reported due to electrocution (n=67). The highest number of elephant deaths (anthropogenic) occurred during the monsoon season, with Ranchi division reporting the most mortalities, followed by East Singhbhum and Saraikela. At the village level, the analysis revealed that areas characterized by higher road densities and reduced forest cover experienced high elephant mortalities. This pattern suggests that increased infrastructure development and habitat degradation may be contributing to the escalation of human-elephant conflicts in these regions. These findings underscore the urgent need for conservation actions, including reforestation, establishment of protected corridors, improved infrastructure planning, and awareness generation at the local level to reduce elephant mortalities and overall human elephant conflict in Jharkhand.